PENGARUH PENDEKATAN SAINTIFIK BERBANTUAN AUGMENTED REALITY TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN MATEMATIKA - Sari, Yunita; Suwangsih, Erna; Eka Putri, Hafiziani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to find out how the application of learning with a scientific approach assisted by augmented reality has an impact on students' ability to think critically in learning mathematics. Using a quasi-experimental research method consisting of a control group as a comparison and an experimental group as a group that will receive treatment in the form of the application of a scientific approach assisted by augmented reality in learning mathematics. Data were collected through a critical thinking ability test used to measure the critical thinking abilities of students in the experimental class and the control class after treatment. The results of this study indicate that students' basic abilities in critical thinking in learning mathematics are influenced by the scientific approach assisted by augmented reality. The scientific approach using augmented reality can effectively improve students' ability to think critically after being applied during learning activities. This is indicated by the achievement and improvement of critical thinking abilities of students in the experimental class better than students in the control class. Keywords: augmented reality, critical thinking skill, scienthific approach